Resveratrol suppresses OSCC invasion and migration by regulating macrophage polarization via Syk signaling pathway - Li, Weibo; Qi, Ying; Li, Yafei; Liu, Lu; Dong, Xiaodan; Li, Bo (Frontiers in Immunology, 2025)
IntroductionAn increasing amount of evidence indicates that the metastasis in oral squamous cell carcinoma (OSCC) is closely associated with the polarization phenotype of tumor-associated macrophages (TAMs). Resveratrol (RES) has been demonstrated to exert an inhibitory effect on the invasion and migration of OSCC cells. However, the mechanism by which RES inhibits OSCC invasion and migration remains to be fully elucidated.MethodsRES for reprogramming TAMs (R-RES group) and RES group were used to interfere with the polarization of tumor-associated macrophages (TAMs). RT-qPCR, ELISA, Western blotting, immunofluorescence staining, transwell and wound-healing assays were used to investigate the anti-tumor mechanism of RES.ResultsR-RES reprogramed TAMs from M2 to M1 phenotype. RES promoted M1 polarization of TAMs and inhibited M2 polarization of TAMs. In mechanism, inhibition of Syk signaling pathway in TAMs attenuated the invasive and migratory ability of CAL27 cells through promoting M1 polarization of TAMs and inhibiting M2 polarization of TAMs.ConclusionsRES suppresses OSCC invasion and migration by regulating the polarization phenotype of TAMs via Syk signaling pathway, further elucidating the anti-tumor mechanism of RES.